Analisis Kebijakan Imigrasi dalam Upaya Mencegah Penyelundupan Orang dan Imigran Gelap di Indonesia (Imigran Rohingya) - Maulidi, Maulidi; Ahmad Burhan Hakim (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Etymologically, the terms emigration, immigration and transmigration all come from the Latin discussion of migration, which means population movement. The movement of people from one place to another, near or far. So, the definition of migrant is the large-scale movement of people from one place to another. Rohingya is a Muslim ethnic group that has lived in Myanmar for centuries. They are a minority, because the majority of Myanmar's population adheres to Buddhism. The government's policy is already underway by providing food and clothing assistance and refugee camps for the Rohingya ethnic group, but many rejections of Rohingya refugees are due to a lack of appreciation for what has been given to them. It would be better for these Rohingya refugees to be returned to Bangladesh on an island specifically for their people where British organizations have raised funds for them.